2018
DOI: 10.1002/2017gl075788
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Scattering of Radiation Belt Electrons by Off‐Equatorial Magnetosonic Waves

Abstract: Fast magnetosonic (MS) waves are commonly regarded as electromagnetic waves that are characteristically confined within ±3° of the geomagnetic equator. We report two typical off‐equatorial MS events observed by Van Allen Probes, that is, the 8 May 2014 event that occurred at the geomagnetic latitudes of 7.5°–9.2° both inside and outside the plasmasphere with the wave amplitude up to 590 pT and the 9 January 2014 event that occurred at the latitudes of—(15.7°–17.5°) outside the plasmasphere with a smaller ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…The large density of ambient cold electrons ( N e > 230 cm −3 ) indicates that the satellite was in the afternoon sector (magnetic local time, MLT ~ 15.3–18.6) of the plasmasphere ( L ~ 4.6–5.8). In the plasmasphere, the ratio of equatorial plasma frequency to electron cyclotron frequency ( f pe / f ce > 30) is much higher than the typical values ( f pe / f ce < 10) reported in the past (e.g., Horne et al, ; Li et al, ; J. Li, Ni, et al, ; Maldonado et al, ; Ni et al, ). In the energy spectrum of hot protons (>0.1 keV) at 90° pitch angle, the phase space density of the 5‐ to 30‐keV protons is obviously larger than those at other energies, indicating that there are significant proton ring distributions near the magnetic equator on the duskside (MLAT ~ 8.4°–0.8° and MLT ~ 15.5–18.6 hr).…”
Section: Observation Of Low‐harmonic Ms Waves and Butterfly Distributmentioning
confidence: 78%
See 1 more Smart Citation
“…The large density of ambient cold electrons ( N e > 230 cm −3 ) indicates that the satellite was in the afternoon sector (magnetic local time, MLT ~ 15.3–18.6) of the plasmasphere ( L ~ 4.6–5.8). In the plasmasphere, the ratio of equatorial plasma frequency to electron cyclotron frequency ( f pe / f ce > 30) is much higher than the typical values ( f pe / f ce < 10) reported in the past (e.g., Horne et al, ; Li et al, ; J. Li, Ni, et al, ; Maldonado et al, ; Ni et al, ). In the energy spectrum of hot protons (>0.1 keV) at 90° pitch angle, the phase space density of the 5‐ to 30‐keV protons is obviously larger than those at other energies, indicating that there are significant proton ring distributions near the magnetic equator on the duskside (MLAT ~ 8.4°–0.8° and MLT ~ 15.5–18.6 hr).…”
Section: Observation Of Low‐harmonic Ms Waves and Butterfly Distributmentioning
confidence: 78%
“…Recently, wave‐particle interaction is put forward to explain the formation of butterfly distribution far away from the magnetopause. MS waves are believed to be a candidate mechanism responsible for the butterfly formation through Landau resonance (Horne et al, ; Li, Yu, et al, ; Xiao et al, ; Yang et al, ), transit time scattering (Bortnik & Thorne, ; Li et al, ; J. Li, Ni, et al, ; Ni et al, , ), and bounce resonance (Chen et al, ; Li & Tao, ; Maldonado et al, ; Shprits, ; Tao & Li, ). Landau resonance occurs when the parallel phase velocity ( ω / k ∥ ) of waves equals to the electron velocity parallel to background magnetic field ( v ∥ ; Artemyev et al, ) and the minimum resonant energy can be obtained according to the study of Horne et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Ni et al () also surveyed the occurrence characteristics of outer zone relativistic electron butterfly distribution based on Van Allen Probes measurements. Local wave‐particle interactions between electrons and magnetosonic (MS) waves, similar to those in the outer radiation belt (Hua et al, , ; Ma et al, ; Ni et al, , ), can drive such butterfly PADs at L = 2.4 (Li et al, ). Moreover, Albert et al () performed simulations of electron phase space density (PSD) due to the combined scattering by plasmaspheric hiss, lightning‐generated whistlers, ground‐based very low frequency (VLF) transmitters, and MS waves at L = 2, demonstrating that the butterfly PADs can occur when the cross diffusion in pitch angle and energy is properly included.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MS waves have caught much attention because, by resonating with particles, they play a crucial role in radiation belt dynamics. On the one hand, numerous studies have found that these emissions are able to produce electron butterfly distributions via Landau resonance and bounce resonance energization (Horne et al, ; Shprits, ; Bortnik and Thorne, ; Li JX et al, ; Li LY et al, ; Ni BB et al, , ; Tao X and Li X, ; Xiao FL et al, ). On the other hand, MS waves are also found capable of interacting with protons through cyclotron resonance (Xiao FL et al, ; Fu S et al, ).…”
Section: Introductionmentioning
confidence: 99%